2022
DOI: 10.3748/wjg.v28.i4.402
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection: How does age influence the inflammatory pattern?

Abstract: The inflammatory pattern during Helicobacter pylori ( H. pylori ) infection is changeable and complex. During childhood, it is possible to observe a predominantly regulatory response, evidenced by high concentrations of key cytokines for the maintenance of Treg responses such as TGF-β1 and IL-10, in addition to high expression of the transcription factor FOXP3. On the other hand, there is a predominance of cytokines associated with the Th1 and Th17 responses among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…Approximately 50% of the global population is infected by Helicobacter pylori, 1 that causes various diseases including peptic ulcer disease and gastric cancer. [2][3][4][5][6] Recent studies have demonstrated that H. pylori eradication therapy has a beneficial effect on reducing the risk of gastric cancer development. [7][8][9] Active eradication of H. pylori infection has been attempted in East Asian countries, 10 where H. pylori and gastric cancer are prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of the global population is infected by Helicobacter pylori, 1 that causes various diseases including peptic ulcer disease and gastric cancer. [2][3][4][5][6] Recent studies have demonstrated that H. pylori eradication therapy has a beneficial effect on reducing the risk of gastric cancer development. [7][8][9] Active eradication of H. pylori infection has been attempted in East Asian countries, 10 where H. pylori and gastric cancer are prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in adults, there is a predominant Th1 response, with higher mucosal levels of IFN-γ and IL12p70 [ 75 ]. Adults also have an increased Th17 response, with higher levels of IL-17A and IL-23 and lower concentrations of TGF-β1, with a cytokine profile more associated with epithelial damage [ 76 ]. Another mechanism involved in this crosstalk involves antimicrobial peptides such as defensins, molecules known to be active against bacteria, viruses, fungi, and protozoa, which are increased in H. pylori -induced gastritis [ 77 ].…”
Section: The Effect Of H Pylori On Gastric Microbiotamentioning
confidence: 99%
“…These responses in children focus on Treg cells with subsequent higher IL-10 and transforming growth factor (TGFβ) production. 32,33 In conclusion, additional studies on children are needed to obtain a more comprehensive insight into the effect of probiotics on H. pylori infection.…”
Section: Food and Function Papermentioning
confidence: 99%